Development of a cyanide content measurement method in salt metls for steel hardening using Raman spectroscopy - Stergaršek, Andrej (Acta chimica slovenica, 2002)
The development of a measurement method for the determination of cyanide content in salt melts for steel hardening using Raman spectroscopy is shown. The laser beam and the signal areled through the glass fibre extension, so the sensitive measuring equipment can be in separate room from the salt bath furnaces. A method of complete sampling and measurement automatisation is also proposed.
Keywords: cianid; določanje; Ramanska spektroskopija